Nanomaterials for the treatment of bacterial infection by photothermal/photodynamic synergism - Yan, Zhaochen; Wang, Danqiu; Gao, Yun (Frontiers in Bioengineering and Biotechnology, 2023)
In the past few decades, great progress has been made in the field of nanomaterials against bacterial infection. However, with the widespread emergence of drug-resistant bacteria, people try their best to explore and develop new antibacterial strategies to fight bacteria without obtaining or increasing drug resistance. Recently, multi-mode synergistic therapy has been considered as an effective scheme for the treatment of bacterial infections, especially the combination of photothermal therapy and photodynamic therapy with controllable, non-invasive, small side effects and broad-spectrum antibacterial characteristics. it can not only improve the efficiency of antibiotics, but also do not promote antibiotic resistance. Therefore, multifunctional nanomaterials which combine the advantages of PTT and PDT are more and more used in the treatment of bacterial infections. However, there is still a lack of a comprehensive review of the synergistic effect of PTT and PDT in anti-infection. This review first focuses on the synthesis of synergistic photothermal/photodynamic nanomaterials, and discusses the ways and challenges of photothermal/photodynamic synergism, as well as the future research direction of photothermal/photodynamic synergistic antibacterial nanomaterials.